Quick and Dirty: Some Psychosocial Costs Associated with the Dark Triad in Three Countries - JONASON, Peter K. (Institutional Knowledge at Singapore Management University, 2013)
The current study provides the first examination of the relationship between life history indicators and the Dark Triad traits in an international sample drawn from the U.S. (n = 264), Singapore (n = 185), and Poland (n = 177). In all three samples, the Dark Triad traits were associated with psychosocial costs, although there were more links in the Singaporean and Polish samples than in the American sample. In the U.S., the quality of one’s romantic relationships and psychopathy were negatively correlated. Narcissism was higher in the Polish and American samples than in the Singaporean sample. Men scored higher than women did regardless of location and the sex difference in the individual differences in life histories was mediated by the Dark Triad composite. Results suggest the Dark Triad are related to a volatile socioecology composed of psychosocial costs in the familial, romantic, and platonic relationships.